2014
DOI: 10.1681/asn.2013040430
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 Receptor Autoantibodies and Clinical Outcome in Patients with Primary Membranous Nephropathy

Abstract: Membranous nephropathy (MN) is the most common cause of nephrotic syndrome in adults, with an uncertain clinical outcome. The characterization of the phospholipase A 2 receptor (PLA 2 R) as the major target antigen in primary MN and the detection of circulating autoantibodies in these patients is a major advance in understanding this disease. To test whether PLA 2 R antibody levels reflect disease activity or clinical outcome, we performed a prospective multicenter study of 133 adult patients with primary MN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
228
3
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(276 citation statements)
references
References 19 publications
23
228
3
11
Order By: Relevance
“…As in other studies, the authors confirmed that the aPLA2R levels decline before the development of remissions of proteinuria and that such remissions can develop weeks or months after the discontinuation of treatment (7)(8)(9). Perhaps most important, the level of aPLA2R at the end of treatment predicted the long-term outcomes.…”
supporting
confidence: 81%
“…As in other studies, the authors confirmed that the aPLA2R levels decline before the development of remissions of proteinuria and that such remissions can develop weeks or months after the discontinuation of treatment (7)(8)(9). Perhaps most important, the level of aPLA2R at the end of treatment predicted the long-term outcomes.…”
supporting
confidence: 81%
“…2 Genetic evidence of the involvement of PLA2R in IMN came from the genome-wide association study identifying PLA2R and DQA1 as genes accountable for the genetic susceptibility to IMN. 3 Clinical confirmation that anti-PLA2R antibodies are relevant in MN is evident from studies showing an association between high levels of anti-PLA2R and active disease, 4,5 poor clinical outcome at 5 years, 5,6 and less chance of spontaneous remission. 7 Failure to render patients anti-PLA2R seronegative by immunosuppression therapy is associated with high risk of relapse.…”
mentioning
confidence: 99%
“…10 Furthermore, high anti-PLA2R1 antibody titers at presentation appear to correlate with subsequent poor renal outcome in most cases, but some patients with high autoantibody titers at onset exhibit a sharp decrease of anti-PLA2R1 activity and disease remission. 11,12 The treatment of iMN is controversial. 13,14 Kidney Disease Improving Global Outcomes (KDIGO) guidelines recommend a supportive symptomatic treatment with blockers of the RAS and diuretics in all patients with iMN, and immunosuppressive therapy only in the case of renal function deterioration or persistent nephrotic syndrome.…”
mentioning
confidence: 99%